Measuring emergent mechanical changes in cytoskeletal ensembles in vitro using QCM-D - Amari, Victoria N.; Kerivan, Emily M.; Reinemann, Dana N. (Frontiers in Cell and Developmental Biology, 2025)
This work presents a protocol for using a quartz crystal microbalance with dissipation monitoring (QCM-D) to measure emergent cytoskeletal mechanics in reconstituted actomyosin systems. Cytoskeletal ensembles exhibit emergent behaviors that cannot be solely inferred from the properties of their constituent molecules. The underlying design principles and mechanisms governing this collective behavior remain poorly understood. Previous work suggests that cytoskeletal filaments, particularly actin, function as force sensors that regulate motor protein activity, influencing contraction, force generation, and cellular shape during movement. To investigate these emergent mechanics, we developed a novel approach utilizing QCM-D to study reconstituted actomyosin bundle systems. Our results demonstrate that QCM-D is capable of detecting viscoelastic changes in actomyosin bundles in response to molecular-scale perturbations, including variations in concentration, nucleotide state, and actin-binding affinity. These findings support the role of actin as a mechanical force-feedback sensor and establish QCM-D as a powerful, complementary technique to optical trapping and fluorescence imaging for probing cytoskeletal ensemble mechanics and motor protein interactions.